Sex-linked hybrid sterility in a butterfly (2007)
Recent studies, primarily in Drosophila, have greatly advanced our understanding of Haldane’s rule, thetendency for hybrid sterility or inviability to affect primarily the heterogametic sex (Haldane 1922). Although dom-inance theory (Turelli and Orr 1995) has been proposed as a general explanation of Haldane’s rule, this remains tobe tested in female-heterogametic taxa, such as the Lepidoptera. Here we describe a novel example of Haldane’s rulein Heliconius melpomene (Lepidoptera; Nymphalidae). Female F1offspring are sterile when a male from French Guianais crossed to a female from Panama, but fertile in the reciprocal cross. Male F1s are fertile in both directions. Similarfemale F1sterility occurs in crosses between French Guiana and eastern Colombian populations. Backcrosses andlinkage analysis show that sterility results from an interaction between gene(s) on the Z chromosome of the Guianarace with autosomal factors in the Panama genome. Large X (or Z) effects are commonly observed in Drosophila,but to our knowledge have not been previously demonstrated for hybrid sterility in Lepidoptera. Differences in theabundance of male versus female or Z-linked versus autosomal sterility factors cannot be ruled out in our crosses ascauses of Haldane’s rule. Nonetheless, the demonstration that recessive Z-linked loci cause hybrid sterility in a femaleheterogametic species supports the contention that dominance theory provides a general explanation of Haldane’s rule(Turelli and Orr 2000).